1997
DOI: 10.1111/j.1439-037x.1997.tb00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Agronomic and Physiological Aspects of Salt Tolerance in Cotton (Gossypium hirsutum L.)

Abstract: Evaluation of commonly grown cotton {Gossypium hirsutum L.) genotypes under saline environment may help to cope with the venture of the crop failure in salt-affected soils. In a pot experiment, four cotton genotypes were grown to compare their relative performance on a sandy clay loam soil (original ECe = 1.9 dS m ') salinized with a salt mixture (Na2SO4, NaCl, CaCl2, MgSO4 in the ratio of 9:5:5:1 on equivalent basis) to EQ levels of 10 and 20 dS m '. The crop was raised to the flower initiation stage. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 11 publications
(13 reference statements)
8
41
1
1
Order By: Relevance
“…5). Reduction in dry matter production with increasing salinity level was noticed by a number of researchers (Abd-Ella and Shalaby 1993; Leidi and Saiz 1997;Qadir and Shams 1997;Ashraf and Ahmad 1999;Basal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…5). Reduction in dry matter production with increasing salinity level was noticed by a number of researchers (Abd-Ella and Shalaby 1993; Leidi and Saiz 1997;Qadir and Shams 1997;Ashraf and Ahmad 1999;Basal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in their character effectiveness have also been reported among varieties of different species including wheat (Akhtar, et al, 1994, 1998. Saqib, et al, 1999 and cotton (Qadir andShams, 1997, Ashraf andAhmad, 2000).The differential behavior of plant species may be helpful for exploitation of these soils by growing fairly tolerant genotypes. This paper reports the results of different studies pertaing to seed germination in Petri dishes, solution culture, and ion uptake behavior and field performance of nine wheat genotypes in different ecological zones of the Punjab province under natural saline field condition.…”
Section: Introductionmentioning
confidence: 97%
“…Also, both the average cotton yield and IWP for A3 and D4 were higher than for F. These results indicate slightly increased cotton growth when some salinity in the irrigation water is present. The yield-promoting effect of some soil salinity has been reported in several studies (e.g., Qadir and Shams 1997;Ashraf and Ahmad 2000;Ashraf 2002;Henggeler 2004). For instance, Vulkan-Levy et al (1998) found that with more water being applied, cotton yields increased with an increase in salinity.…”
Section: Crop Yieldsmentioning
confidence: 99%
“…Mulched drip irrigation, which saves water and increases water use efficiency as compared to furrow irrigation (Ibraginmov et al 2007), is widely used in the area to irrigate cotton, a major cash crop in Xinjiang (Hou et al 2009). Cotton yields generally decrease with a reduction in irrigation, irrespective of whether conventional irrigation technologies or drip irrigation is used (Singh et al 2010;Ü nlü et al 2011), and are also limited by poor quality of irrigation water and related problems of soil salinization (Leidi and Saiz 1997;Vulkan-Levy et al 1998;Qadir and Shams 1997;Henggeler 2004;Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%